A simulation of the separate climate effects of middle-atmospheric and troposheric CO2 doubling - Sigmond, M.; Siegmund, P.C.; Manzini, E.; Kelder, H.M. (2004)
The separate climate effects of middle-atmospheric and tropospheric CO2 doubling have been simulated and analyzed with the ECHAM middle-atmosphere climate model. To this end, the CO2 concentration has been separately doubled in the middle-atmosphere, the troposphere, and the entire atmosphere, and the results have been compared to a control run. During NH winter, the simulated uniformly doubled CO2 climate shows an increase of the stratospheric residual circulation, a small warming in the Arctic lower stratosphere, a weakening of the zonal winds in the Arctic middle-atmosphere, an increase of the NH midlatitude tropospheric westerlies, and a poleward shift of the SH tropospheric westerlies. The uniformly doubled CO2 response in most regions is approximately equal to the sum of the separate responses to tropospheric and middle-atmospheric CO2 doubling. The increase of the stratospheric residual circulation can be attributed for about two-thirds to the tropospheric CO2 doubling and one-third to the middle-atmospheric CO2 doubling. This increase contributes to the Arctic lower-stratospheric warming and, through the thermal wind relationship, to the weakening of the Arctic middle-atmospheric zonal wind. The increase of the tropospheric NH midlatitude westerlies can be attributed mainly to the middle-atmospheric CO2 doubling, indicating the crucial importance of the middle-atmospheric CO2 doubling for the tropospheric climate change. Results from an additional experiment show that the CO2 doubling above 10 hPa, which is above the top of many current GCMs, also causes significant changes in the tropospheric climate.